Marketing, Technology and Customer Commitment in the New Economy Proceedings of the 2005 Academy of Marketing Science (AMS) Annual Conference - Spotts, Harlan E.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This volume includes the full proceedings from the 2005 Academy of Marketing Science (AMS) Annual Conference held in Tampa, Florida, entitled Marketing, Technology and Customer Commitment in the New Economy. It include papers aimed to create awareness of the issues, trends, and advances associated with current global marketing challenges.   Founded in 1971, the Academy of Marketing Science is an international organization dedicated to promoting timely explorations of phenomena related to the science of marketing in theory, research, and practice. Among its services to members and the community at large, the Academy offers conferences, congresses and symposia that attract delegates from around the world. Presentations from these events are published in this Proceedings series, which offers a comprehensive archive of volumes reflecting the evolution of the field. Volumes deliver cutting-edge research and insights, complimenting the Academy’s flagship journals, the Journal of the Academy of Marketing Science (JAMS) and AMS Review. Volumes are edited by leading scholars and practitioners across a wide range of subject areas in marketing science.  .
Education: Innovations in Course Control and Delivery -- Internet Marketing Issues -- Retailing Track: Differences Among Consumer Segments -- Sales: Managing Customer Relationships -- B2B: Trust, Loyalty, and Interfirm Governance -- Doctoral Session: Buyer Behavior Issues -- International: Consumer Behavior Issues and Global Marketing -- The Pursuit of Happiness: A Worthy Focus for Marketers? -- Consumer Perceptions in Services Research -- Strategy: Insights on Networks and Relationship Strategy -- Retailing: Atmospherics Role in the Shopping Experience -- Research: Qualitative and Quantitative Approaches to Market Research -- Doctoral Session: Consumer Perceptual Potpourri -- Strategy: Organizational Learning and Marketing Strategy -- Focusing on Improving Salesperson Job Performance and Job Attitude -- Merchandising and Store Patronage: Examining Determinants of Retail Customer Intentions -- IMC: Advertising: Deception, Emotion and Wireless Message -- Services: Understanding Service Quality and Relationship Quality in Service Firms -- Consumer Loyalty Research: What do We Know? -- Doctoral Session: Technology and Marketing -- Store Image –Theory, Research and Reality: A South Africa Perspective -- Consumer Behavior Potpourri -- Ethics: Regulation and Self-Regulation in Markets -- Technology Issues in Consumer Behavior -- Electronic Marketing Issues -- Measurement Issues in Marketing -- Globalization Potpourri -- Ethical and Legal Issues -- Marketing Potpourri -- Purchasing Motivations: Generations, Products and Attitudes -- Doctoral Session: Marketing Strategy Issues -- International: Marketing Strategy Issues and Global Marketing -- International: Marketing Management Issues and Global Marketing -- Special Session: Academy of Marketing Science: Lamb, Hair, & McDaniel Outstanding Marketing Teachers -- Social and Non-Profit Marketing -- Services: Customer-Firm Interactions and Communications in Service Industries -- B2B: Sustaining and Maintaining Supply Chains -- Marketing Mix, Environment, and Strategy -- Doctoral Session: Relationship Marketing Issues -- Marketing Strategy: Insights on Market Orientation -- Retailing: A Look at Various Promotional Issues -- Doctoral Dissertation Award Winner Finalists Presentations -- Understanding Ourselves: Identity, Brands, and Consumption.
Keywords: Marketing; Leadership; Sales management; Marketing; Business Strategy/Leadership.; Sales/Distribution.